Handbook of the Sociology of Mental Health
XIX, 628 p. 9 illus.
Keywords: This handbook describes the ways in which society shapes the mental health of its members and further shapes the lives of those who have been identified as mentally ill. With regards to the social origins of mental health, this handbook covers both the social conditions that lead to the behavior defined as mental illness and the way in which the concept of mental illness is socially constructed around those behaviors. This handbook also covers a third body of work that examines socially conditioned responses to mental illness on the part of individuals and institutions along with the ways in which these responses affect the lives of persons with mental illness. Sections include: I: Introduction: Alternative Understandings of Mental Health. II: Observing Mental Health in the Community. III: The Social Distribution of Mental Illness. IV: Social Antecedents of Mental Illness. V: Social Consequences of Mental Illness. V I: Institutional Contexts of Mental Illness. VII: Social Continuities. Each of these viewpoints survey the field in a critical manner, evaluating theoretical models in light of the best available empirical evidence. Distinctively sociological approaches are highlighted by means of explicit comparison to perspectives characterizing related disciplines such as psychology, psychiatry, and anthropology. This volume seeks to record where the field has been, to identify its current location and to plot its course for the future.